Ferns and lycophytes of remnants in Amazônia Maranhense, Brazil - Silva Junior, Wagner Ribeiro da; Ferreira, Alessandro Wagner Coelho; Ilkiu-Borges, Anna Luiza; Fernandes, Rozijane S. (Biota Neotropica, 2020)
Abstract This work is an inventory of ferns and lycophytes of remnants in Amazônia Maranhense. The data provided are the results of collections made from 2010-2011 and 2016-2019 in various municipalities of Maranhão in the Amazonian part of the state. Sixty-four species of ferns and lycophytes, in 36 genera and 18 families, were recorded. Of these, 24 species are new records for Maranhão and four are new records for the Northeast Region of Brazil. The most representative family was Pteridaceae (23 species), followed by Polypodiaceae (7 species). The predominant life forms were terrestrial (37 species) and epiphytic (15 species); the latter is the highest number of epiphytic species recorded for a fern and lycophyte inventory in Maranhão. The data support the need for collecting ferns and lycophytes in Amazônia Maranhense to better understand the flora of these groups in the state.